OPTIMAL PARALLEL PREPROCESSING ALGORITHMS FOR TESTING WEAK VISIBILITY OF POLYGONS FROM SEGMENTS - HSU, F. R.; CHANG, R. C.; LEE, R. C. T. (Parallel algorithms and applications, 1993)
For an n-gon P, we say P is weakly visible from segment s if any point on P is visible from at least one point of the segment. In this paper, we present an optimal preprocessing algorithm which runs in O(logn) time using O(n) processors under the concurrent read exclusive write parallel random access machine model such that after preprocessing, it takes O(logn) time to test if P is weakly visible from a given segment using a single processor.